Analysis of parabolic antennas for radio telescopes and the development of encryption methods for radio astronomical images - Ting, Kung Chuang (2022)

(untitled)
An analysis on the performance of Cassegrain reflector antennas has been presented. In this study, we have adopted the design parameters for the Cassegrain configuration used in the Atacama Large Millimeter Array (ALMA) project. The focal-length-to-diameter ratio f/D of the primary reflector has been adjusted to investigate the optimum performance of the antenna. In this study, signal frequency at the high edge of ALMA band 1, i.e. 45 GHz has been selected. The results obtained from the physical optics simulation show that the aperture efficiency of the antenna is at its optimum (i.e. 80.36%) when f/D ranges from 0.5 to 0.6. The radiation characteristics at this range of ratio are found to be similar. The radius of the secondary reflector and edge taper Te which correspond to the optimum aperture efficiencies ranges from 371 mm to 372 mm and 10.64 dB to 10.75 dB, respectively. With the rapid progress in space technology development, a lot of digital images are transmitted back to ground telescope receiver. Thus, image security plays a significant role during the transmission process. Existing algorithms in image security were developed based on Latin squares, DNA sequence etc. However, the suitability of the techniques is questionable and high cost was needed. In this study, several development of encryption methods for radio astronomical images had been iii studied and proposed. The proposed algorithms include Development of Bit level Scrambling Encryption for Radio Telescope Imageries, Bit-levels Encryption for RGB Telescope Images, Bit-levels Encryption for RGB Telescope Images, Design of Encryption Algorithm in Combined Spatial and Frequency Domains for Telescope Grayscale and Bayer Images, and Combined Spatial and Frequency Domains in Algorithm of RGB Color Image Security for Telescope Images. The outputs were evaluated using histogram distribution, NPCR, UACI, PSNR, SSIM and information entropy. The results showed that this algorithm has better performance compared to other recently developed algorithms.